UNSUR EKSTRINSIK DALAM CERPEN ASRAN KARYA TRISNI SUMARDJO - Sum, Tengku Muhammad (Universitas Lancang Kuning, 2018)
This analysis proves that in Indonesian Anthology of Short Stories, especially short story written by Trisno Sumardjo entitled Asran, there are three extrinsic elements are founded. They are: social, economic, and educational elements. This analysis finds that the character of Asran is interesting to discuss because this character has different sides in his life: social, economic, and educational sides which can contribute to maturize the readers in understanding the life.